Copper(II) Complexes of N, N‐Diisopropylpicolinamide – Solvatochromic and Thermochromic Phase Change of a Monomeric Complex to a Ferromagnetically Coupled Dimeric Complex. Issue 27 (19th July 2013) - Lumb, Isha; Hundal, Maninder Singh; Corbella, Montserrat; Gómez, Verónica; Hundal, Geeta
Abstract: The synthesis and characterization of mononuclear [Cu(L)2 (Cl)2 ] (1 ), dinuclear [CuCl(L)2 (μ‐Cl)2 ] (2 ), and another mononuclear complex [Cu(L)2 (ClO4 )2 ] (3 ) with a bidentate N, N ‐diisopropylpicolinamide ligand (abbreviated L) are described. Complexes1 and2 were obtained from the same reaction mixture and show thermo‐ and solvatochromic behavior. Complex1 shows irreversible thermochromism by changing into2 upon heating at 160 °C. These two complexes also show solvatochromism in various solvents. The coordination geometry of the metal ions in1 and3 is distorted octahedral, whereas2 has Cu II ions in a distorted square‐pyramidal geometry. Variable‐temperature magnetic susceptibility measurements for the dinuclear copper complex show a ferromagnetic interaction between the Cu II ions. The chromotropism has been attributed to a change in geometry from octahedral with terminal chloride ligands to a distorted square‐pyramidal coordination with bridging chloride ions. Abstract : A monomer, [Cu(L)2 (Cl)2 ] (1, L = N, N ‐diisopropylpicolinamide), and a ferromagnetically coupled dimer, [Cu(L)(Cl)2 ]2 (2 ), are obtained from the same reaction mixture. They show thermo‐ and solvatochromic behavior owing to the change in coordination geometry from a terminally bonded octahedral copper center to a distorted square‐pyramidal copper center with bridging chloride ions.